Carbono almacenado y biomasa en especies de árboles comerciales del bosque de terraza media de la Concesión Forestal Raíces Amazónicas, distrito de Mazán, Loreto. 2022 - Maldonado Ganoza, Celia Cristina (2024)
The research study lasted for four months, with data collection conducted over two consecutive months in March and April 2022, within the Raíces Amazónicas forest concession located in the district of Mazán, province of Maynas, department of Loreto. The objective was to quantify the biomass and stored carbon in commercial tree species in a medium terrace forest within the Raíces Amazónicas concession, district of Mazán, Loreto, in 2022. Evaluations of commercial tree species were carried out within logging plot twelve (PC 12) covering an area of 502.35 hectares, subdivided into 32 strips. Data collection was conducted through direct measurement (forest census), using a field data log where the most relevant characteristics of each commercial tree (common name, diameter at breast height, commercial height, total height) were recorded. Dauber's formula (Dauber et al., 2008, p. 9) was used to calculate biomass, and data normality was determined using the Kolmogorov-Smirnov test, while variable correlation was assessed using Spearman's non-parametric test. The identification of commercial species was carried out using herbarium specimens taken to the Herbarium Amazonense of the National University of the Peruvian Amazon. A total of 338 trees were recorded, grouped into 15 botanical families. The total biomass was 1021.624 tons, and the stored carbon was 5105.855 tC.